Sleep Quality in Academic Performance of Engineering Students - López, Pedro Pablo Rosales; Pacheco, Mercedes Puca; Calanchi, Enrique Tacuri; Vega, Ismael Armando Arévalo; Lázaro, Gonzalo Pablo Villa; Gayoso, Valeria Luciana Mayandía; Marín, Antony Tuesta (Journal of Ecohumanism, 2025)
This research corresponds to a completely randomized blocked factorial experimental design. The independent variable Sleep Quality is used as a factor and the Control of academic progress (evaluations) as blocks, the response variable is academic performance. The research was carried out at the Faculty of Industrial Engineering of a public university in the city of Lima - Peru. To determine the quality of sleep, the Pittsburgh Index was used and to determine the response variable, the average grades of the students from the first evaluations of the semester were used. The results were consistent with the hypotheses proposed by the authors, that is; sleep quality affects the academic performance of students.